Midwives' descriptions of avoidable causes of negative perinatal outcomes - Kagiso P. Tukisi (AOSIS, 2023)
Background: The Perinatal Problem Identification Programme (PPIP) is used to rule out the avoidable and nonavoidable causes of negative maternal and perinatal outcomes through file audits. Perinatal Problem Identification Programme serves as a tool for midwives and obstetricians to pinpoint missed opportunities that could prevent avoidable causes of negative perinatal outcomes. Aim: The study aimed to describe and explore the avoidable causes of negative perinatal outcomes in Bojanala District through the lens of the midwife. Setting: This study was conducted in the two selected facilities in the Bojanala District in the North West Province of South Africa. Methods: The study derived from a larger study that focused on midwives' experiences of obstetric triage in the Bojanala District. A qualitative, exploratory and descriptive research design was used with purposive sample of nine midwives. Participants had over 5 years of clinical midwifery experience and were employed in the Bojanala District. Semi-structured interviews were utilised with data analysed using Colaizzi's descriptive method of data analysis. Results: Three major themes with eight subthemes emerged. Midwives noted space constraints, medicine and medical supply constraints, and constraints in availability of medical equipment. Access to identified constraints would enable prompt and appropriate management. Conclusion: The study highlighted the experience of midwives in accessing needed space, medicines, medical supplies and equipment, potentially impacting negative perinatal outcomes. Contribution: This study provides insight into administratively related avoidable causes of negative perinatal outcomes through the lens of frontline maternity care providers - midwives. Findings should be of particular utility to health service managers working to reduce maternal mortality and morbidity.